Development of technology elements for growing of perennial sorghum - Adamen, F. F.; Saplev, A. V.; Kudinov, S. V. (Acta Agraria Debreceniensis, 2014)
Optimal sowing time for perennial sorghum under irrigation is when soil temperature at the depth of sowing reaches up to 10–11 °С, harvesting for the green mass has to be done when panicle is situated on the stem in 10 sm from the flag leaf and hight of cut must be 11 sm.